Representation matters: (re)articulating collective identities in a postcolonal world - Hoffmann, Anette; Peeren, Esther (Rodopi, 2010)
In the twenty-first century, the terms "representation" and "identity" seem to have gone out of fashion. The essays collected here, however, seek to demonstrate the extent to which they continue to matter in the social, political and cultural strug.
Includes bibliographical references and index. - Description based on print version record
Keywords: Aufsatzsammlung; Repräsentation; Kulturelle Identität; Gruppenidentität; Postkolonialismus; Nichtwestliche Welt